Frontal Brain EEG Activation in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Electroencephalographic (EEG) activity of 117 unmedicated children (66 aged 4 years, 51 aged 8 years) with attention deficit/hyperactivity disorder (ADHD) was analyzed at the Department of Child and Adolescent Psychiatry and Psychotherapy, Central Institute of Mental Health, Mannheim, Germany.